Allergic rhinitis as a possible risk factor for malocclusion: a case–control study in children. Issue 4 (28th September 2012) - Luzzi, Valeria; Ierardo, Gaetano; Viscogliosi, Annamaria; Fabbrizi, Miriam; Consoli, Giuliana; Vozza, Iole; Vestri, Annarita; Polimeni, Antonella
<x xml:space="preserve">Abstract</x> Background Prolonged oral respiration is known to cause postural alterations, which can lead to dental malocclusions. Allergic rhinitis, a common cause of upper airway obstruction in children, must therefore be seen as a possible risk factor in the development of malocclusions. Aim Aim of this study was to investigate the association between allergic rhinitis and malocclusions in primary and early‐mixed dentition. Design A case–control study was carried out involving 275 Italian children aged 5–9. The case group and the control group were composed of 125 individuals affected by malocclusions and by 150 healthy patients, respectively. Through a questionnaire, we assessed the presence of professionally diagnosed allergic rhinitis. Data were analysed to identify associations between these variables and the presence of malocclusions. Results Children with a history of allergic rhinitis had a threefold increased risk to develop one or more dento‐skeletal alterations [OR = 3.16; 95% CI (1.79–5.58), P < 0.001]. Statistically significant associations were found between allergic rhinitis and the development of posterior crossbite and increased overjet. No significant association was found for anterior openbite. Conclusions Allergic rhinitis is a significant risk factor for the development of malocclusions in general and is associated with the development of posterior crossbite and increased overjet.